HASIL BELAJAR PSIKOMOTOR FISIKA SISWA SMA DENGAN MENGGUNAKAN MEDIA SIMULASI VIRTUAL PhET - Sepriani, Rina; Nasir, Muhammad; ', Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack:  The study aims determine the psicomotor of physics students with the use of media in the simulation virtual PhET in SMAN 4 Pekanbaru. This type of research that is used is quasi eksperimental, with the posttest-only control groups design. The population of this research is all students in class X SMAN 4 Pekanbaru, with samples of class X1 as experiment of 31 students  and class X2 as control class of 31 students. The data in this research is a score posttest of psikomotor and analysis with descriptive and inferensial analysis. The analysis of data showed absortion of student in the experiment class is higher than the control class on each indicator of psikomotor. The absorption in class experiment is 90,68 with gread category. Result of inferensial analysis using independent sample t-test, the significant is 0,310 and 1,025, because  and t aitmatic is smaller with t table, then the hypothesis accepted, so there are not significant differences between the psicomotor of students in the experimental class by applying medium simulation virtual PhET with the control class that not applying medium simulation virtual PhET with a level of trust 95 %. With this be concluded that applying of medium simulaton virtual PhET for skill psikomotor physics students.